2004
DOI: 10.1046/j.1365-2958.2003.03851.x
|View full text |Cite
|
Sign up to set email alerts
|

Molybdate transport and its effect on nitrogen utilization in the cyanobacterium Anabaena variabilis ATCC 29413

Abstract: SummaryMolybdenum is an essential component of the cofactors of many metalloenzymes including nitrate reductase and Mo-nitrogenase. The cyanobacterium Anabaena variabilis ATCC 29413 uses nitrate and atmospheric N 2 as sources of nitrogen for growth. Two of the three nitrogenases in this strain are Mo-dependent enzymes, as is nitrate reductase; thus, transport of molybdate is important for growth of this strain. High-affinity transport of molybdate in A. variabilis was mediated by an ABC-type transport system e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 61 publications
1
55
0
Order By: Relevance
“…ModA binds molybdate in the periplasm, ModB is the transmembrane component of the permease, and ModC provides the energizer function on the cytoplasmic side of the membrane (for reviews see Grunden & Shanmugam, 1997;Self et al, 2001). Similar systems for molybdate transport have been characterized in Rhodobacter capsulatus (Wang et al, 1993), Azotobacter vinelandii (Luque et al, 1993;Mouncey et al, 1995Mouncey et al, , 1996, Staphylococcus carnosus (Neubauer et al, 1999) and Anabaena variabilis (Thiel et al, 2002;Zahalak et al, 2004). Immediately following the modC gene, another ORF, designated modD, has been found in E. coli and R. capsulatus, the deletion of which has no phenotypic effect Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…ModA binds molybdate in the periplasm, ModB is the transmembrane component of the permease, and ModC provides the energizer function on the cytoplasmic side of the membrane (for reviews see Grunden & Shanmugam, 1997;Self et al, 2001). Similar systems for molybdate transport have been characterized in Rhodobacter capsulatus (Wang et al, 1993), Azotobacter vinelandii (Luque et al, 1993;Mouncey et al, 1995Mouncey et al, , 1996, Staphylococcus carnosus (Neubauer et al, 1999) and Anabaena variabilis (Thiel et al, 2002;Zahalak et al, 2004). Immediately following the modC gene, another ORF, designated modD, has been found in E. coli and R. capsulatus, the deletion of which has no phenotypic effect Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…For example, a number of genes encoding proteins have been shown to be involved in bacterial resistance to such heavy metals as cobalt, zinc, cadmium, arsenic, copper, molybdenum and silver (Nies, 1995(Nies, , 1999Grunden and Shanmugam, 1997;Rensing et al, 1997Rensing et al, , 1999Brown et al, 2002;Parro and Moreno-Paz, 2003;Zahalak et al, 2004;Basim et al, 2005;Bencheikh-Latmani et al, 2005;Braz and Marques, 2005;Hu et al, 2005;Methe et al, 2005;Permina et al, 2006) and had higher transcript levels in sediment-grown cells (Table 7).…”
Section: Locus Idmentioning
confidence: 99%
“…However, increased expression of the molybdate ABC type transporter genes, modA, modB and modC (Table 7), might also be explained by the fact that there is an increased demand for molybdenum under nitrogenfixing conditions. Earlier studies have shown that increased expression of molybdenum transporter genes is frequently associated with nitrogen-fixing conditions, because molybdenum is an essential component of nitrogenase proteins involved in nitrogen fixation (Grunden and Shanmugam, 1997;Parro and Moreno-Paz, 2003;Zahalak et al, 2004).…”
Section: Locus Idmentioning
confidence: 99%
“…Culturing experiments with modern strains of diazotrophic (nitrogen-fixing) cyanobacteria generally indicate that rates of nitrogen fixation and overall growth become impacted by Mo availability once concentrations fall to within the ∌1-10-nM range (45)(46)(47)(48)(49). Some strains seem to show resilience to Mo scarcity until concentrations fall below ∌5 nM (48), but in general there seems to be a sharp change in overall growth rates, cell-specific nitrogen fixation rates, and stoichiometric growth status within the 1-10-nM range.…”
Section: Marine Euxinia: Global Effects Of Regional Ocean Chemistrymentioning
confidence: 99%